Rancang bangun sistem informasi manajemen proyek menggunakan dashboard dengan metode pureshare di pt. Skill menara pratama berbasis website - Maya Utami Dewi; Achmad Muazim (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2022)
This thesis research conducted at PT. Skill Menara Pratama with difficulty is project document that hold by each project coordinator make project manager difficult to monitor and evaluate every project that being done, also potentially loss of project data. Distribution of project data are not well distributed. Limitations of project manager work time to monitoring and evaluation work because the projects handled are often more than 1 (one) a simultaneously. Development of this project management information system using the dashboard with pureshare method. developing application based on the website while for programming using HTML and PHP with MySQL as database server.. The research was carried out by development with R&D approaching which resulted prototype product of management information system application of research. test result tested with research instrument in the form of questionnaire with 10 (ten) questions, final conclusion from this research result prototype product can be used, and can be developed further. The result of development resulted prototype software application that tested has been able to solve the problem related to project document held by each field coordinator, has been able to solve the problem of dissemination of data project that not well distributed, has been able to ease in storage and search of project document and make it as backup of hardcopy documents, and has made it easy for project managers, directors and employers to read progress on the job so as to improve the quality of decisions policy in projects quickly, appropriately and more efficiently in their implementation.